THE CREDIT SUPPLY CHANNEL OF MONETARY POLICY TRANSMISSION MECHANISM: AN EMPIRICAL INVESTIGATION OF ISLAMIC BANKS IN PAKISTAN VERSUS MALAYSIA - Shah, Syed Muhammad Abdul Rehman; Rashid, Abdul (Journal of Islamic Monetary Economics and Finance, 2019)
The transmission mechanism of monetary policy is explained through the relationshipsbetween a change in money supply and the level of real income. Monetary policytransmits to the real sector through several different channels. Such channels includethe interest rate channel, the exchange rate channel, the asset-pricing channel, the creditsupply channel, and the bank balance sheet channel. This paper empirically investigatesthe credit supply channel of monetary policy and explores the differential impact ofmonetary policy on credit supply of Islamic banks in Pakistan versus Malaysia. Therobust two-step System-Generalize Method of Moments (GMM) estimator is appliedon an unbalanced panel dataset over the period 2005-2016. While estimating the effectsof three alternative measures of monetary policy on banks’ credit supply, several bank-specific variables are included in the specification as control variables. We providestrong evidence on the existence of credit supply channel in the baseline models forboth countries and differential impact of monetary policy through Islamic banks inPakistan versus Malaysia in the extended models. Our findings suggest that there isa vital need to consider the nature of Islamic banks while devising the instrumentsof an effective monetary policy in countries with dual banking system like Pakistan,Malaysia, Indonesia, Bahrain, Saudi Arabia, Qatar and others.